Bürgerbeteiligung zur Gemeindeentwicklung im ländlichen Raum – Möglichkeiten der Methodenkombination am Beispiel von Steinach im Kinzigtal - C. Uhlendahl, Thomas (Raumforschung und Raumordnung | Spatial Research and Planning, 2015)
The federal state of Baden-Wuerttemberg requires public participation for fundings on communal development. Various methods and instruments of public participation do exist now for years. Until 2014, the federal state of Baden-Wuerttemberg has funded wisdom councils (BürgerInnenRäte) to integrate the public who would normally not participate in any community work on local politics. Several thematic workshops were organized in Steinach, Kinzigtal in 2013 so as to create a development concept for the local community. Complementing the workshops a wisdom council was founded supporting an application for the Landessanieungsprogramm (programme to redevelop local communities). The results of the workshops were integrated into the development concept and were the basis for the process of the wisdom council. Without major changes, the proposed solution suggested by the wisdom council was converted into an application to the Landessanierungsprogramm. While demonstrating the innovative synergetic combination of methods of public participation, this essay additionally shows the advantages for communal planers in charge of engineering development concepts for rural communities which are affected by demographic and structural change.